2018
DOI: 10.1002/fam.2516
|View full text |Cite
|
Sign up to set email alerts
|

Method to characterize the fire behavior of materials assemblies

Abstract: Summary The fire behavior of various large samples polymers assemblies is an under‐researched topic. In fire risk assessment, the resultant heat release rate of burning different combustibles has to be known. To highlight interactions between components, 2 types of configurations were tested: juxtaposed and layered materials, using a specific radiant panel setup. For juxtaposed assemblies, results indicated that the more flammable component acted as an accelerator for the global combustion kinetics. For layere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In common cases, the polymer assemblies are examined by an intermediate cone calorimeter in the horizontal position. However, some recent studies found more hazardous effects using vertical sample orientation (Pizzo et al , 2008; Leventon and Stoliarov, 2013; Vincent et al , 2018). So, the modification in fire load, sample orientation, test room conditions can generate more authentic test data from existing intermediate fire tests.…”
Section: Fire Test Methods For Claddingsmentioning
confidence: 97%
See 1 more Smart Citation
“…In common cases, the polymer assemblies are examined by an intermediate cone calorimeter in the horizontal position. However, some recent studies found more hazardous effects using vertical sample orientation (Pizzo et al , 2008; Leventon and Stoliarov, 2013; Vincent et al , 2018). So, the modification in fire load, sample orientation, test room conditions can generate more authentic test data from existing intermediate fire tests.…”
Section: Fire Test Methods For Claddingsmentioning
confidence: 97%
“…Though the data on flame behaviour of cladding materials are limited and most of the research data are based on bench-scale testing for single material (McKenna et al , 2019; McLaggan et al , 2020). However, different research work suggested that combined fire performance of multiple materials can give significantly different results compared to singular test material (Chow and Han, 2006; Vincent et al , 2018). Therefore, it is assumed that the combined impact study of multiple materials using bench-scale or small-scale testing will give more accurate and practical results for the cladding system in the future.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%